Abstracts from the 6th Infection Control Africa Network Congress - Wangai, Helen Wambui; Sikhosana, Mpho; Jombwe, Josephat (Antimicrobial Resistance and Infection Control, 2020)
Antimicrobial Resistance and Infection Control, Vol. 6, No 1, p.2-11